2021
DOI: 10.1186/s12894-021-00918-0
|View full text |Cite
|
Sign up to set email alerts
|

Buccal mucosal graft urethroplasty for anterior urethral stricture, experience from a low-income country

Abstract: Background/purpose This study was conducted to present our experience in urethral mucosal graft urethroplasty to repair urethral stricture, as the first experience in our context. Methods This is a prospective hospital-based study that had been designed to review management outcomes of buccal mucosal graft urethroplasty for anterior urethral stricture from January 2017 to January 2019. Results The tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
6
2
3
Order By: Relevance
“…In comparison to buccal mucosal graft urethroplasty, substitution urethroplasty with ATEPP also shows good results. In a study by Sami Mahjoub Taha Awad et al 20 ( Table 4 ), their success rate with buccal mucosal graft urethroplasty was 90% with a 10% re-stricture rate. In our study success rate with ATEPP urethroplasty was 82% with an 18% failure rate.…”
Section: Discussionmentioning
confidence: 97%
“…In comparison to buccal mucosal graft urethroplasty, substitution urethroplasty with ATEPP also shows good results. In a study by Sami Mahjoub Taha Awad et al 20 ( Table 4 ), their success rate with buccal mucosal graft urethroplasty was 90% with a 10% re-stricture rate. In our study success rate with ATEPP urethroplasty was 82% with an 18% failure rate.…”
Section: Discussionmentioning
confidence: 97%
“…Refractory urethral strictures to initial management present surgical challenges to the reconstructive surgeon because it is considered a complex stricture that requires tissue transfer or staged urethroplasty [ 6 , 7 ]. It has been reported in the literature that BMGs in complex anterior urethral strictures have lately become a well-established management modality for bulbar and penile urethral strictures compared with penile fasciocutaneous flap and scrotal skin [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Especially for those who are not suitable for anastomosis or excision [ 6 ]. Furthermore, the BMG has an advantage over other tissues as it resembles urethral mucosa and is easily harvested [ 7 ]. In addition, it has been found that repeating endoscopic management such as dilatation and DVIU is not beneficial in a complex resistant stricture [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Awad et al 6 , en un estudio prospectivo con 60 pacientes, en un periodo de dos años, evaluaron los resultados del uso de injertos de mucosa oral (BMG) para el manejo de la EU anterior, con un éxito del 90% (aunque no describieron cómo lo definieron), y una recurrencia del 10%, encontraron que las complicaciones más frecuentes eran la infección del tracto urinario y infección de sitio operatorio (ISO).…”
Section: Uso De Injertos O Colgajosunclassified